KAJIAN PEMASARAN TELUR AYAM RAS DAN PROSPEK PENGEMBANGANNYA DI PERUSAHAAN GRACIA FARM TIMOR-LESTE - Rofino Maria Pinto; Triana Dewi Hapsari; Rudi Hartadi (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
Gracia Farm is a company which produces eggs of layer chicken in Timor- Leste. This study aims to determine: marketing channels of eggs that are applied by the Company Gracia Farm Timor-Leste; marketing margin of eggs in the Company Gracia Farm Timor-Leste; and the prospects of development of eggs in the Company Gracia Farm Timor-Leste. Determination of the study area is done intentionally (purposive method) i.e. Ermera District of Timor-Leste. The research method is used descriptive and analytical methods. The sample in this research is used snowball sampling. The analysis is used Margin Marketing and SWOT analysis. The results of research show there are three marketing channels of chicken eggs in Gracia Farm are marketing channel I (Company Gracia Farm-Distributor-Wholesalers- Consumer), marketing channel 2 (Company Gracia Farm-Distributor- Retailer-Consumer Trader) and marketing channel 3 (Gracia Farm Company-Distributors-Wholesalers-Retailers-Consumers Traders). Margin marketing of eggs in Gracia Farm Timor-Leste on the three marketing channels are Rp 6.618 / kg (marketing channel I), Rp 8.997 / kg (marketing channel 2), and Rp 9.119 / kg (marketing channel 3), Prospects for the development of eggs (laying) in company Gracia Farm located at the position of White area which means that eggs (laying) both to be developed .